Characterizing Deformability of Drug Resistant Patient-Derived Acute Lymphoblastic Leukemia (ALL) Cells Using Acoustic Tweezers. Issue 1 (December 2018) - Liu, Hsiao-Chuan; Gang, Eun; Kim, Hye; Lim, Hae; Jung, Hayong; Chen, Ruimin; Abdel-Azim, Hisham; Shung, K.; Kim, Yong-Mi
Abstract The role of cell mechanics in cancer cells is a novel research area that has resulted in the identification of new mechanisms of therapy resistance. Single beam acoustic (SBA) tweezers are a promising technology for the quantification of the mechanical phenotype of cells. Our previous study showed that SBA tweezers can be used to quantify the deformability of adherent breast cancer cell lines. The physical properties of patient-derived (primary) pre-B acute lymphoblastic leukemia (ALL) cells involved in chemotherapeutic resistance have not been widely investigated. Here, we demonstrate the feasibility of analyzing primary pre-B ALL cells from four cases using SBA tweezers. ALL cells showed increased deformability with increasing acoustic pressure of the SBA tweezers. Moreover, ALL cells that are resistant to chemotherapeutic drugs were more deformable than were untreated ALL cells. We demonstrated that SBA tweezers can quantify the deformability of nonadherent leukemia cells and discriminate this mechanical phenotype in chemotherapy-resistant leukemia cells in a contact- and label-free manner.